Pretrichodermamide A Biosynthesis Reveals the Hidden Diversity of Epidithiodiketopiperazines - Fan, Jie; Ran, Huomiao; Wei, Peng‐Lin; Li, Yuanyuan; Liu, Huan; Li, Shu‐Ming; Hu, Youcai; Yin, Wen‐Bing (Angewandte Chemie International Edition, 2023)
Fungal epidithiodiketopiperazines (ETPs) possess large structural diversity and complexity due to modifications of the cyclodipeptide skeleton. Elucidation of the biosynthetic pathway of pretrichodermamide A (1) in Trichoderma hypoxylon revealed a flexible catalytic machinery of multiple enzymes for generating ETP diversity. Seven tailoring enzymes encoded by the tda cluster are involved in 1 biosynthesis, that is, four P450s TdaB and TdaQ for 1,2‐oxazine formation, TdaI for C7′‐hydroxylation, and TdaG for C4, C5‐epoxidation, two methyltransferases TdaH for C6′‐ and TdaO for C7′‐O‐methylation, and a reductase TdaD for furan opening. Gene deletions led to the identification of 25 novel ETPs, including 20 shunt products, indicating the catalytic promiscuity of Tda enzymes. Particularly, TdaG and TdaD accept various substrates and catalyze regiospecific reactions at different stages of 1 biosynthesis. Our study not only uncovers a hidden library of ETP alkaloids, but also helps to understand the hidden chemical diversity of natural products by pathway manipulation. The biosynthetic route of fungal epidithiodiketopiperazines (ETPs) was revealed by elucidating the biosynthesis of pretrichodermamide A. Diverse ETP derivatives, including 25 novel compounds, were characterized from tda gene deletion mutants, indicating divergent metabolic pathways of ETP intermediates and enzyme catalytic promiscuity.